Posterior Spinal Fusion With Pedicle Screws in Patients With Idiopathic Scoliosis and Open Triradiate Cartilage: Does Deformity Progression Occur?. Issue 7 (October 2016) - Sponseller, Paul D.; Jain, Amit; Newton, Peter O.; Lonner, Baron S.; Shah, Suken A.; Shufflebarger, Harry; Bastrom, Tracey P.; Marks, Michelle C.; Betz, Randal R.
Abstract : Background: Anterior-posterior spinal fusion (APSF) is the traditional treatment for patients with idiopathic scoliosis and open triradiate cartilage (OTRC). Our goals were to assess whether posterior-only spinal fusion (PSF) with pedicle screws can halt deformity progression as effectively as APSF in patients with OTRC, and whether selection of the distal fusion level influences curve progression. Methods: We studied a prospective multicenter database to identify all children with 2-year radiographic and clinical follow-up who were 11 years or younger with Risser grade 0 and OTRC who were treated with (1) PSF (OTRC-PSF group, N=20); or (2) APSF (OTRC-APSF group, N=9). A reference group was constructed of 20 children who were 18 years or younger with Risser grade 4 or 5 and closed triradiate cartilage (CTRC) and who were treated with PSF (CTRC-PSF group) and matched in preoperative curve magnitude and type to the OTRC-PSF group. The 3 groups were compared with respect to operative time, blood loss, length of hospital stay, and radiographic and functional outcomes (significance, P <0.05). Results: OTRC-APSF patients had significantly longer operative time ( P <0.01), greater blood loss ( P =0.02), and longer hospital stays ( P <0.01) than OTRC-PSF patients. At 2 years, 7 (35%) OTRC-PSF patients had >10 degrees of curve progression compared with no patients in the OTRC-APSF group ( P =0.042) and 1 patient in the CTRC-PSF group ( P =0.018). The OTRC-PSF group had the highest number of patients fused to the stable vertebra. Of the 11 OTRC-PSF patients fused to 1 vertebra short of stable, 6 (55%) had >10 degrees of curve progression. Of the 9 OTRC-PSF patients fused to at least the stable vertebra or lower, only 1 (11%) had curve progression. There were no significant differences in Scoliosis Research Society outcome scores between OTRC-PSF patients who did and those who did not have >10 degrees of curve progression. Conclusions: PSF with pedicle screws was associated with curve progression in a significantly greater proportion of patients with OTRC compared with APSF. Not fusing to stable was also associated with curve progression in patients treated with PSF but not APSF. Level of Evidence: Level III—therapeutic.